A new species of the clingfish genus Trachelochismus from bay and estuarine areas of New Zealand (Teleostei: Gobiesocidae) - Conway, Kevin W.; Stewart, Andrew L.; King, Cragen (Zootaxa, 2017)
Trachelochismus aestuarium, new species, is described on the basis of 120 specimens, 10.1–45.5 mm SL, collected from shallow (0–29 meters depth) bay and estuarine areas along the coast of New Zealand. It is distinguished from congeners (T. melobesia and T. pinnulatus) by a combination of characters, including features of the cephalic sensory system, adhesive disc papillae, and colouration in life, head shape, and gill-raker, fin ray and vertebrae counts. Phylogenetic analyses of mitochondrial loci (cytrochrome c oxidase subunit 1 and 12S ribosomal RNA) and one nuclear locus (zic family member 1) for all three species of Trachelochismus and two outgroup taxa resulted in phylogenetic hypotheses in which T. aestuarium is the sister taxon to either T. pinnulatus (mitochondrial loci) or T. pinnulatus + T. melobesia (ZIC1). A new terminology is introduced for the superficial neuromasts arranged in rows on the surface of the head in members of Trachelochismus.